2014
DOI: 10.1016/j.biomaterials.2013.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release from a mechanically-stimulated thermosensitive self-heating composite hydrogel

Abstract: a b s t r a c tTemperature has been extensively explored as a trigger to control the delivery of a payload from environment-sensitive polymers. The need for an external heat source only allows limited spatiotemporal control over the delivery process. We propose a new approach by using the dissipative properties of a hydrogel matrix as an internal heat source when the material is mechanically loaded. The system is comprised of a highly dissipative hydrogel matrix and thermo-sensitive nanoparticles that shrink u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…Among different hydrogel systems being covalently crosslinked, Poly(2-hydroxyethyl methacrylate) (PHEMA) has received considerable attention as a biocompatible hydrogel with tunable mechanical properties (Voldrich et al, 1975;Lou et al, 2004;Young et al, 1998;Traian, 2001;Moghadam et al, 2014). HEMA monomers have a hydrophilic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Among different hydrogel systems being covalently crosslinked, Poly(2-hydroxyethyl methacrylate) (PHEMA) has received considerable attention as a biocompatible hydrogel with tunable mechanical properties (Voldrich et al, 1975;Lou et al, 2004;Young et al, 1998;Traian, 2001;Moghadam et al, 2014). HEMA monomers have a hydrophilic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Longterm degradation mirrors the rate of tissue development in load-bearing tissues like cartilage and nucleus pulposus where the healing process is slow. [37][38][39] In parallel, the high damping properties observed in the develop hydrogels provided load and crack resistance under the loading conditions of such tissues. 12,18 It has been already shown that HEMA-based hydrogels can partially degrade when they are cross-linked to some natural polysaccharides molecules such as chitosan, 22 dextran-based molecules, 7,40 hyaluronic acid and poly(lactic acid) PLA.…”
Section: Discussionmentioning
confidence: 98%
“…Review Abdel-Sayed & Pioletti delivery with cell receptors activation, which is essential for an enhancement of the tissue regeneration [88]. Indeed, mechanical loading has been shown to activate cell receptors to growth factors involved in the regeneration of cartilage [89][90][91], therefore a temporally adapted delivery induces maximum potency of the drug.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%